PROGNOSTIC VALUE OF ALBI, EZ-ALBI AND PALBI SCORES FOR REBLEEDING RISK IN PATIENTS WITH UPPER GASTROINTESTINAL BLEEDING DUE TO ESOPHAGEAL VARICEAL RUPTURE (Vietnam Journal of Community Medicine, 2026)
Objective: To describe clinical characteristics and evaluate the prognostic value of ALBI, EZ-ALBI, and PALBI scores in predicting rebleeding risk in patients with upper gastrointestinal bleeding due to esophageal variceal rupture.Subject and methods: A cross-sectional study with analytical components was conducted in 81 patients with upper gastrointestinal bleeding due to esophageal variceal rupture at Ca Mau General Hospital from June 2025 to January 2026.Results: Males accounted for 63.7%, with a mean age of 57.0 ± 11.9 years. Prior variceal bleeding was reported in 9.9%. Common comorbidities included hypertension (24.7%), diabetes (13.6%), hepatitis B (11.1%), and hepatitis C (3.7%). The rebleeding rate was 6.2%. ALBI and PALBI stratifications differed significantly by rebleeding outcome (p < 0.001), whereas EZ-ALBI did not (p = 0.073). Rebleeding clustered in higher ALBI (grades 2-3) and PALBI groups. On ROC analysis, ALBI showed the highest discrimination (AUC 0.879), followed by PALBI (0.845) and EZ-ALBI (0.834).Conclusion: ALBI and PALBI demonstrated useful risk stratification and predictive performance for rebleeding, with ALBI showing a trend toward better discrimination, while EZ-ALBI showed no significant association.
Keywords: ALBI score, EZ-ALBI score, PALBI score, prognostic value, rebleeding, esophageal variceal bleeding.